Eosinophil infiltration and degranulation in oesophageal mucosa from adult patients with eosinophilic oesophagitis: a retrospective and comparative study on pathological biopsy. Issue 11 (23rd March 2006) - Mueller, S; Aigner, T; Neureiter, D; Stolte, M
Abstract : Aim: To examine eosinophil infiltration and degranulation in 50 oesophageal biopsy specimens from 30 patients (21 men, 9 women; mean 39 years) with eosinophilic oesophagitis, by haematoxylin and eosin staining and immunohistochemistry. Methods: Immunohistochemistry was carried out using a monoclonal antibody for human eosinophilic major basic protein (MBP). Eosinophils were counted in three high power fields (×40) and degranulation, as quantified by extracellular MBP immunostaining, was scored on a scale of 1–4. Morphological changes (basal cell hyperplasia, elongation of papillae and dilatation of intercellular spaces) were scored on a 1–4 scale on sections stained with haematoxylin and eosin. Results: Numbers of intraepithelial eosinophils were significantly higher with MBP immunostaining than with haematoxylin and eosin staining (mean 109.6 v 80.6; p<0.001), whereas numbers of eosinophils were considerably correlated (r = 0.794). Eosinophil degranulation was higher in the distal oesophagus. Additionally, basic morphological changes were markedly associated with eosinophil infiltration. Extracellular deposition of eosinophil-MBP and eosinophil infiltration in subepithelial connective tissue, present in the biopsy specimens, were detected by immunohistochemistry. Conclusion: Numbers of eosinophils and degranulation are underestimated by haematoxylin and eosin staining. Immunohistochemistry detected up to two times more eosinophils than routine haematoxylin and eosin staining. Moreover, eosinophil-MBP immunoreactivity in extracellular regions indicates the release of toxic eosinophil granule proteins and gives further evidence for a causative role of eosinophils with regard to structural changes in eosinophilic oesophagitis. Immunohistochemistry may serve as a useful diagnostic tool to support the morphological differential diagnosis of eosinophilic oesophagitis and gastro-oesophageal reflux disease.